Fundamentals of industrial robotics [ - Nelsen, Wayne; Wayne, Lockwood (Meridian Education Corporation, 2004)
This video includes actual footage from major manufacturers of robots as well as industries using robots in manufacturing and other processes. In its introduction, the tape compares industrial robots to science fiction robots and offers reasons for the increase interest in robots. It then covers basic terminology, fundamental concepts, robots system components, classification of robots, programming and limitations of robots. A section on industrial applications presents a representatives sample of applications for which industrials robots are used in manufacturing, materials handling, quality control and so fourth. The video also describes many of the emerging career opportunities in and related to industrial robots systems...system design, system maintenance, system supervision and system distribution